Karyotype of some species of Chara and Nitella (Charophyta) from Bangladesh - Khatun, Wahida; Ud-Deen, Md Mosleh; Kabir, Golam (Bangladesh Journal of Botany, 2010)
Karyotypic analysis of Chara corallina Linn., C. vulgaris Linn., C. gymnopitys Linn. and Nitella translucens Ag. collected from natural habitats revealed that C. corallina has n=42, C. vulgaris and Chara gymnopitys have n=14 while Nitella translucens has n=18 chromosomes. All the species had differences in individual chromosome length, total chromatin length, total frequency between the complements of their chromosomes. The proposed standard karyotype formula were 6Lm + 2Mm +26Msm + 6S1m + 2S2m for Chara corallina, 4Mm + 8S1m + 2S2m for Chara vulgaris, 6Mm + 4S1m + 2S2sm +2S2m for Chara gymnopitys and 6Lm + 2Lsm + 6Mm+ 2Msm + 2S1m for Nitella translucens. Key words: Chara; Nitella; Karyotype; Green algae; Bangladesh DOI: 10.3329/bjb.v38i2.5150 Bangladesh J. Bot. 38(2): 205-207, 2009 (December)